2017
DOI: 10.3389/fphys.2017.00010
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Effects of Pharmacological Blockers of Cardiac Autonomous Control Using Variability Parameters

Abstract: Objective: The aim of this study was to identify the most sensitive heart rate and blood pressure variability (HRV and BPV) parameters from a given set of well-known methods for the quantification of cardiovascular autonomic function after several autonomic blockades.Methods: Cardiovascular sympathetic and parasympathetic functions were studied in freely moving rats following peripheral muscarinic (methylatropine), β1-adrenergic (metoprolol), muscarinic + β1-adrenergic, α1-adrenergic (prazosin), and ganglionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Heart rate variability (HRV) analysis with search for new algorithms is commonly employed to measure alterations in autonomic tone with predictive value in diseases ( Campos et al, 2013 ). We have identified the CV of the heart rate as a sensitive measure of autonomic dysfunction ( Miyabara et al, 2017 ) and independently associated with vascular atherosclerosis ( Pereira et al, 2017 ). In this study, we found that CV of intrapartum cardiotocography FHR is an independent predictor of neonatal acidemia and Apgar scores.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate variability (HRV) analysis with search for new algorithms is commonly employed to measure alterations in autonomic tone with predictive value in diseases ( Campos et al, 2013 ). We have identified the CV of the heart rate as a sensitive measure of autonomic dysfunction ( Miyabara et al, 2017 ) and independently associated with vascular atherosclerosis ( Pereira et al, 2017 ). In this study, we found that CV of intrapartum cardiotocography FHR is an independent predictor of neonatal acidemia and Apgar scores.…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs occur esterified or as free fatty acids cleaved from the plasma membrane by phospholipases (PL: A 1, A 2, C, and D). Once released, PUFAs can be further metabolized [8], act as second messengers [9], interact with membrane proteins [10], and/or alter the mechanical properties of the bilayer [11-15]. Yet distinguishing between some of these modalities has been quite challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, recent structure-function studies have demonstrated that lipids could also contribute to channel gating via direct lipid-protein interaction. As the direct effect of PUFAs on voltage-gated Na + , K + , and Ca 2+ channels has been reviewed elsewhere [10], we will focus on other cation channels (Table 1) that do not necessarily share a common topology or PUFA-binding signature sequence, such as: glutamate receptors (N-methyl-D-aspartate receptor, NMDA), transient receptor potential (TRP) channels, mechanotransduction channel complexes, pentameric ligand-gated ion channels (pLGICs), and Ca 2+ -activated large-conductance K + (BK) channels.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, when comparing concentric and eccentric contractions, it is worth noting that the overwhelming majority of research is carried out on lower limb tendons (patellar and Achilles). This apparent bias may be due to their specific role within energy retention and power amplification during movement [ 31 , 32 ]. Thus, both the patellar and Achilles tendon have high functional significance and, hence, high research interest.…”
Section: Are Eccentric Contractions More Effective Than Concentricmentioning
confidence: 99%